EKSISTENSI RAHASIA DAGANG SEBAGAI KEKAYAAN INTELEKTUAL: KAJIAN SEJARAH, RUANG LINGKUP, JANGKA WAKTU, DAN PENEGAKAN HUKUM MELALUI ANALISIS KASUS - Muhammad Aria Fachri Irawan; Muhamad Kholid (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Trade secrets are part of Intellectual Property Rights that hold economic value and require legal protection. This study aims to analyze the regulation of trade secrets in Indonesia under Law No. 30 of 2000, covering the history, scope, duration of protection, and legal sanctions for violations. The method used is normative juridical with a descriptive-analytical approach. The results show that trade secret protection is indefinite as long as the information remains confidential, holds economic value, and is properly maintained. Violations may be subject to civil and criminal sanctions, and settlement through civil channels has proven effective in providing compensation.